Considering the alternatives: lessons from Israel’s meat substitutes initiatives - Grosglik, Rafi; Raz, Aviad; Shahar, Danit R.; Avieli, Nir (Frontiers in Sustainable Food Systems, 2024)
As one of the industry leaders in the field of alternative proteins, Israel provides an interesting and important test case for examining explicit and implicit agendas in the professional and public debate regarding sustainable pathways for alternative proteins. Based on in-depth interviews with key stakeholders in the Israeli food-tech ecosystem and analysis of two recent reports (The Good Food Institute-Israel’s report on the State of Protein Alternative Innovation and the Israel Innovation Authority report), we elucidate and highlight institutional, socio-cultural, socio-technological, and nutritional aspects inherent to the debate on meat substitutes. Looking at the socially constructed classification of meat substitutes in Israel, we explore the regulatory challenges and public discourses and scrutinize sustainability considerations in the context of meat substitutes. Finally, we advocate for diverse solutions to address the multifaceted issues intertwined with meat substitutes, emphasizing the need for more comprehensive research to understand the intricate interplay among distinct categories of meat alternatives.